APPLICATION OF MONITORING RESULTS ON CONTEMPORARY VERTICAL MOVEMENTS OF THE EARTH'S CRUST IN THE SPITAK EARTHQUAKE REGION FOR FURTHER STUDIES (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Data on the Spitak earthquake from scientific studies conducted by specialists were analyzed and consolidated. The differences in the absolute heights of benchmarks, obtained during previous leveling works at the geodynamic polygon of the Spitak Region, were summarized, analyzed, and calculated. Based on these data, a map depicting modern vertical crustal movements in the Spitak earthquake zone was created for the period before the 1988 earthquake, and subsequently for the 1989–1990 period. Another map was generated for the period from 1989–1990 to 2002–2006, illustrating that the rate of crustal subsidence–measured at 9 to 12 mm/year – persisted until 2016. It is currently hypothesized that the Earth's crust in this region continues to subside at the same rate. This hypothesis is supported by data officially provided by the RA Ministry of Emergency Situations, as well as by a map of earthquake epicenters with magnitudes of M ≥ 2.5 recorded in the Amasya, Ashotsk, and Bavra Regions between 01.01.2020–01.03.2022. It is recommended to initiate a project for comprehensive geodynamic monitoring in this region, involving the joint efforts of surveyors, geologists, geophysicists, and seismologists. The data obtained will help clarify the causes of crustal dynamics and their patterns in relation to the stresses resulting from energy accumulation in the Earth's subsurface.
Keywords: earthquake; fault; crust; vertical displacement; geodynamic polygon; leveling; elevation mark